Fashion Confronting Unrelated Sectors. - Maria Antonietta Sbordone; Barbara PIZZICATO; Gianni Montagna; Sonia Seixas (ModaPalavra e-periódico, 2022)
This study aims to reflect on a possible symbiosis between the fashion system and unrelated companies focused on reducing textile waste.